2022
DOI: 10.18393/ejss.1063980
|View full text |Cite
|
Sign up to set email alerts
|

Relative potential of Rhizobium sp for improving the rice-wheat crop in the semi-arid regions

Abstract: Soil Microbiologists have been concentrating on manipulation of rhizosphere microbes in cereals, but many researchers have reported that rhizobia can act as plant growth promoting rhizobacteria (PGPR). Rhizobium species impacted the crop ontogeny by root / endophytic colonization, producing phytohormones, efficient nutrient use and nutrient solubilization / mineralization. Field studies were performed at Soil Bacteriology Section and Soil Chemistry Section, Faisalabad to assess the comparative potential of Rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…(Mung bean) significantly increased nitrogen and leaf protein contents. This results partially agreed with those obtained by [7] concerning wheat plants. Rhizobial bacteria improved wheat, cotton and maize growth by mobilizing more nutrients, and increasing NPK uptake, this may either be due to the ability of rhizobial inoculums to act as PGPR, and solubilize and mobilize nutrients from organic and inorganic sources according to Adnan et al [14].…”
Section: Effects Of Rhizobial Foliar Application On Some Biochemical ...supporting
confidence: 92%
See 1 more Smart Citation
“…(Mung bean) significantly increased nitrogen and leaf protein contents. This results partially agreed with those obtained by [7] concerning wheat plants. Rhizobial bacteria improved wheat, cotton and maize growth by mobilizing more nutrients, and increasing NPK uptake, this may either be due to the ability of rhizobial inoculums to act as PGPR, and solubilize and mobilize nutrients from organic and inorganic sources according to Adnan et al [14].…”
Section: Effects Of Rhizobial Foliar Application On Some Biochemical ...supporting
confidence: 92%
“…Biofertilizer also known microbial inoculants are the substance that either solid or liquid substances contains beneficia1 microbes that have participated in different functions for promoting plant growth. Biofertilizer are environment friendly, inexpensive, and reasonable source that have potential role,, in the plant growth promotion [7]. Many microbiologists of soi1 have been concentrating on manipulation in cereals rhizosphere microbes, but many researchers have found that rhizobial bacteria can act as plant growth of promoting rhizobacteria (PGPR).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PGPR and legumes can form bio-interactions, with roots secreting compounds that promote vigorous plant growth. PGPR also plays a protective role by producing antibiotics to prevent root rot diseases and contribute to overall plant health (Qureshi et al 2022). Moreover, PGPR's contribution extends to macronutrient provision, particularly nitrogen, influencing crop growth (Mendes et al, 2013;Lazcano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%